2020
DOI: 10.1002/qute.201900087
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐Cavity QED with Tunable Nano‐Tip Interaction

Abstract: Quantum state control of two‐level emitters is fundamental for many information processing, metrology, and sensing applications. However, quantum‐coherent photonic control of solid‐state emitters has traditionally been limited to cryogenic environments, which are not compatible with implementation in scalable, broadly distributed technologies. In contrast, plasmonic nano‐cavities with deep sub‐wavelength mode volumes have recently emerged as a path toward room temperature quantum control. However, optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 117 publications
(208 reference statements)
1
21
0
Order By: Relevance
“…-New experiments using tip-enhanced strong coupling to optimize the coupling strength between a plasmonic cavity and a single quantum emitter is described. [18] This work demonstrates a new methodology for optimization of plasmonic cavities. -Förster resonance energy transfer (FRET) between two solidstate quantum emitter systems is demonstrated.…”
Section: Mohamed Benyoucef Anthony Bennett Stephan Götzinger and Cmentioning
confidence: 97%
“…-New experiments using tip-enhanced strong coupling to optimize the coupling strength between a plasmonic cavity and a single quantum emitter is described. [18] This work demonstrates a new methodology for optimization of plasmonic cavities. -Förster resonance energy transfer (FRET) between two solidstate quantum emitter systems is demonstrated.…”
Section: Mohamed Benyoucef Anthony Bennett Stephan Götzinger and Cmentioning
confidence: 97%
“…An interesting recent example of plexciton study has been conducted in the setting of scanning probe nano-optical imaging and spectroscopy (Figure 8). This work by May et al [398], along with a study by Groß et al [397], implemented the scanning optical cavities formed between a nano-optical antenna and the substrate. The authors investigated CdSe/ZnS quantum dots using this scanning cavity approach and observed plexitonic Rabi splitting of 163 meV.…”
Section: Dn Basov Et Al: Polariton Panoramamentioning
confidence: 99%
“…Panels B: Measured PL spectra for the QD, cavity plasmon polariton, weakly coupled system (WC) and strongly coupled states (SC) with coupling strength g = 141 meV. A Lorentzian lineshape representing the redshifted plasmon resonance in the presence of the QD is calculated from the fitted values (SPP QD )[398].…”
mentioning
confidence: 99%
“…In addition to modifying the phase of the near-field by varying the lateral position x relative to the resonator surface, nanotips can also contribute to the crossover from weak to strong coupling, as the vertical position z is tuned. Local modulation of strong coupling has been demonstrated with quantum dot emitters in optical nanoresonators [67,68], but has yet to be implemented with infrared nanostructures. In order to theoretically study these effects, we now generalize the analysis in Sec.…”
Section: Tip-induced Modulation Of Strong Couplingmentioning
confidence: 99%